NOTE ON THE OCCURRENCE OF PHYLLOSTOMIDAE FROM THE LATE HOLOCENE AT LAPA GRANDE DE TAQUARAÇU SITE, LAGOA SANTA, STATE OF MINAS GERAIS, BRAZIL: NOTE ON THE OCCURRENCE OF PHYLLOSTOMIDAE - Chahud, Artur (Acta Biologica Brasiliensia, 2025)
The Lagoa Santa region, located in central Brazil, is rich in fossils and hosts important archaeological and paleontological sites, such as Lapa Grande de Taquaraçu. This site has been archaeologically studied, but the analysis of the archaeofauna remains preliminary. The present study reports a well-preserved specimen of Chrotopterus auritus, found in deposits dated to the Late Holocene. The analyzed material consists of a fragmented mandible (with left and right teeth) and a left humerus, both belonging to the same individual. The species Chrotopterus auritus is found in humid tropical forests of Central and South America, including southern Brazil. It is one of the largest species of the Phyllostomidae family, with a predominantly carnivorous and insectivorous diet. The presence of this specimen at the Lapa Grande de Taquaraçu archaeological site has no direct connection with the human communities of the region, as no signs of human activity were identified on the bones. It is possible that the specimen inhabited the site after its abandonment by human populations.